A ten-year review of neonatal tetanus cases managed at a tertiary health facility in a resource poor setting: The trend, management challenges and outcome - Ogundare, Ezra Olatunde; Ajite, Adebukola Bidemi; Adeniyi, Adewuyi Temidayo; Babatola, Adefunke Olarinre; Taiwo, Adekunle Bamidele; Fatunla, Odunayo Adebukola; Airemionkhale, Alfred; Odeyemi, Oluwapelumi Adeyosola; Olatunya, Oladele Simeon; Oyelami, Oyeku Akibu (PLOS Neglected Tropical Diseases, 2021)
Author summary Neonatal Tetanus (NNT) is a vaccine preventable disease of public health importance still being encountered in clinical practice largely in developing countries however, there are still foci of tetanus cases in the developed world, although exceedingly rare. Tetanus is a toxin mediated disease responsible for the death of hundreds of newborns every year, unfortunately most of these deaths are not recorded because most of the affected babies do not have contact with health facilities. Only 5% of cases are reported to present in health facilities. The Maternal and Neonatal Tetanus Elimination initiative has made remarkable progress as more than three quarter of the priority countries have attained elimination, and the remaining countries seems to be making steady progress over the years. NNT is still being seen in our health facilities. Poor antenatal clinic attendance, unsupervised deliveries, poor cord care, low maternal literacy level and low socio-economic status were some of the major risk factors for NNT in this study. Mortality from NNT is still high as there is no means of ventilatory support for affected babies. There is the need to encourage mothers to attend antenatal care during pregnancy, get vaccinated and have supervised deliveries. There is also the need for public enlightenment campaign on the appropriate and approved cord care methods. It may also be important to consider incorporating tetanus vaccination into the School Health Programme (SHP) to ensure that every female child gets adequate protection before commencement of childbearing.